BRIDGING REGULATION AND PRACTICE: REGIONAL INSIGHTS ON LOCAL BUDGET CORRUPTION AND GOVERNANCE IN SOUTHEAST ASIA - Khoirunnisa Khoirunnisa; Didi Jubaidi (The Indonesian Journal of Public Administration (IJPA), 2025)
Corruption in local government budget management remains a persistent threat to the principles of good governance across Southeast Asia. Despite the presence of formal regulatory frameworks aimed at promoting transparency and accountability, their practical implementation often falls short due to structural, institutional, and political constraints. This study investigates how public regulations influence the enforcement of good governance and explores the challenges faced by law enforcement agencies in combating corruption in regional budgets, with a particular focus on Indonesia and comparative insights from other ASEAN countries. Employing a qualitative approach, the study uses case studies of two Indonesian local governments, combining document analysis, in-depth interviews with key stakeholders, and field observations of budgeting practices. The findings reveal that although regulatory frameworks are generally adequate, their enforcement is undermined by limited bureaucratic capacity, political patronage, and institutional fragmentation. Law enforcement is further hampered by overlapping mandates, weak inter-agency coordination, and uneven resource allocation. Comparative analysis highlights that effective anti-corruption strategies require more than robust legal frameworks—they depend on political will, institutional integrity, and active civic participation. This study contributes both theoretically and practically by bridging the gap between policy and enforcement, offering insights for reform strategies tailored to decentralized governance systems.